Analysis of Value Decrease Loss Reserve Policy (Case Study in PT Bank “X”, Tbk) - Asyraf Firas Abdurrasyid; Evita Puspitasari (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This research is aimed to analyze how banks implement policies regarding impairment for allowance losses after the application of FINANCIAL ACCOUNTING STANDARD STATEMENT 50 and 55, and also to analyze how banks exercise professional judgment in their obligation to implement the impairment of the allowance losses policy.This is a qualitative research, where the case study is used as a method of choice. The case study methods used in this research are Explanation Building and Pattern Matching. The company which is used as a subject of this research is a bank that has gone public and has implemented FINANCIAL ACCOUNTING STANDARD STATEMENT 50 and 55.The result of the analysis using Explanation Building illustrates that the bank has fully implemented FINANCIAL ACCOUNTING STANDARD STATEMENT 55 and there are policies that are discreet to the management. The analysis which uses Pattern Matching indicates that in the process of constructing the impairment for allowance losses policy, the bank has exercised professional judgment principles based on the framework established by the Institute of Chartered Accountants Scotland.Keywords: Accounting Policy, Case Study, Impairment for Allowance Losses, Professional Judgment